Nephronophthisis - Simms, Roslyn J (Nature Publishing Group, 2009)
Nephronophthisis (NPHP) is an autosomal recessive kidney disorder characterized by chronic tubulointerstitial nephritis and leading to end-stage renal failure. NPHP as a renal entity is often part of a multisystem disorder and has been associated with many syndromes including Joubert syndrome (and related disorders) and Senior–Loken syndrome. Recent molecular genetic advances have allowed identification of several genes underlying NPHP. Most of these genes express their protein products, named nephrocystins, in primary cilial/basal body structures. Some nephrocystins are part of adherens junction and focal adhesion kinase protein complexes. This shared localization suggests that common pathogenic mechanisms within the kidney underlie this disease. Functional studies implicate nephrocystins in planar cell polarity pathways, which may be crucial for renal development and maintenance of tubular architecture.